PENGALAMAN IBU HAMIL DALAM MELAKUKAN VCT DI ERA NEW NORMAL - Purba, Gita Adearni; Dewi, Yulia Irvani; Kurniawan3, Didi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Introduction: Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells that causes the body's immune system to decrease, several ways of transmitting HIV, including transmission of HIV from mother to child. To prevent mother to child transmission of HIV, the government targets that by 2022, all pregnant women must detect it early through an HIV test. VCT is an HIV test that is carried out during pregnancy check-ups to determine the HIV status of pregnant women which is carried out voluntarily. In the new custom, the government advises not to visit health facilities too often, but it does not prevent pregnant women from having prenatal check-up. Purpose was to explore the experience of pregnant women in performing VCT in the new normal era. Method was carried out qualitatively with a phenomenological approach, obtained 5 pregnant women who participated in this study using purposive sampling method. Results this study obtained 3 themes: (1) understanding of pregnant women about HIV and HIV prevention, (2) knowledge of pregnant women about VCT, (3) VCT service procedures provided by the Sidomulyo Public Health Center, RI